Chemical and Biological Characterization of the Ethyl Acetate Fraction from the Red Sea Marine Sponge Hymedesmia sp. - Zeinab I. El Sayed; Wafaa H. B. Hassan; Mahmoud M. Abdel-Aal; Shaza M. Al-Massarani; Wael M. Abdel-Mageed; Omer A. Basudan; Mehtab Parveen; Eman Abdelsalam; Sahar Abdelaziz (MDPI AG, 2024)
Hymedesmiidae is one of the largest families of marine sponges and stands out as an exceptional source of variable metabolites with diverse biological activities. In this study, the ethyl acetate fraction (HE) of a Hymedesmia sp. marine sponge from the Red Sea, Egypt, was analyzed for the first time using Ultra-performance liquid chromatography electrospray ionization tandem mass spectrometry (UPLC-ESI-MS/MS) analysis. The analysis tentatively identified 29 compounds in this fraction, including the isolation and identification of six compounds (two pyrimidine nucleosides, one purine, and two pyrimidine bases in addition to one cerebroside) for the first time. The structures of the isolated compounds were established by 1D and 2D NMR (nuclear magnetic resonance), MS (mass spectrometry), and IR (infrared) spectroscopy. Furthermore, the cytotoxic, antioxidant, and antimicrobial activities of the ethyl acetate fraction were evaluated in vitro. The fraction exhibited strong DPPH scavenging activity with an IC50 of 78.7 µg/mL, compared to ascorbic acid as a positive control with an IC50 of 10.6 µg/mL. It also demonstrated significant cytotoxic activity with IC50 values of 13.5 µg/mL and 25.3 µg/mL against HCT-116 and HEP-2 cell lines, respectively, compared to vinblastine as a positive control with IC50 values of 2.34 µg/mL and 6.61 µg/mL against HCT-116 and HEP-2, respectively. Additionally, the ethyl acetate fraction displayed promising antibacterial activity against S. aureus with a MIC value of 62.5 µg/mL, compared to ciprofloxacin as a positive control with MIC values of 1.56 µg/mL for Gram-positive bacteria and 3.125 µg/mL for Gram-negative bacteria. It also exhibited activity against E. coli and P. aeruginosa with MIC values of 250 µg/mL and 500 µg/mL, respectively. Briefly, this is the first report on the biological activities and secondary metabolite content of the ethyl acetate fraction of Hymedesmia sp. marine sponge, emphasizing the potential for further research against resistant bacterial and fungal strains, as well as different cancer cell lines. The ethyl acetate fraction of Hymedesmia sp. is a promising source of safe and unique natural drugs with potential therapeutic and pharmaceutical benefits.